STUDI KASUS PERTANIAN BERBASIS KOMUNITAS - Panji Al Falah; fian, Sofianto; Aditya Saputra; Bagas Setia Ramadhan; Paris Likuwatan (STISIP Widyapuri Mandiri Sukabumi, 2024)
The role of local communities in managing natural resources is becoming increasingly important along with increasing awareness of the importance of sustainability and environmental preservation. This study aims to explore the role of local communities in managing natural resources through a community-based agricultural approach in Indonesia. The method used in this research is a case study with a focus on several villages that have successfully implemented sustainable agricultural practices. Data was collected through in-depth interviews, field observations, and document analysis.The research results show that local communities have rich traditional knowledge about natural resource management, which is often more effective and environmentally friendly than modern practices. Active community participation in decision making, planning and implementation of community-based agricultural activities has been proven to increase the efficiency and sustainability of natural resource management. The success of this sustainable agriculture program is also supported by cooperation between local communities, government and non-government organizations.In addition, this research found that involving local communities in natural resource management can improve their economic and social welfare. Community-based agriculture not only produces higher quality and more diverse agricultural products, but also creates jobs and increases people's income. Education and training provided to the community on sustainable agricultural techniques and environmental conservation also contribute to increasing their awareness and ability to protect and utilize natural resources wisely.However, this research also identified several challenges faced in implementing community-based agriculture, including limited access to modern technology, lack of financial support, and bureaucratic obstacles. Therefore, supportive policies and sustainable initiatives are needed to strengthen the role of local communities in natural resource management.In conclusion, the role of local communities in managing natural resources through community-based agriculture has great potential to support sustainable development and community welfare. With the right support, this approach can become an effective model for sustainable natural resource management in various regions